2020
DOI: 10.2147/idr.s284751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasmid-Mediated AmpC β-Lactamase <em>CITM</em> and <em>DHAM</em> Genes Among Gram-Negative Clinical Isolates</p>

Abstract: Background: Antibiotic resistance mediated by the production of extended-spectrum βlactamases (ESBLs) and AmpC β-lactamases is posing a serious threat in the management of the infections caused by Gram-negative pathogens. The aim of this study was to determine the prevalence of two AmpC β-lactamases genes, bla CITM and bla DHAM , in Gram-negative bacterial isolates. Materials and Methods: A total of 1151 clinical samples were obtained and processed at the microbiology laboratory of Annapurna Neurological Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
7
29
2
3
Order By: Relevance
“…MDR strains were predominant among the isolates of E. coli in comparison to K. pneumoniae . This result was in consistent with previous findings which also reported the rate of MDR in a range of 41.0%–67.7% [ 9 , 20 , 28 , 52 , 60 ] while lower than some other findings [ 8 , 10 ]. In this study, the prevalence of MDR E. coli and K. pneumoniae was 59.3% and 48.8% respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MDR strains were predominant among the isolates of E. coli in comparison to K. pneumoniae . This result was in consistent with previous findings which also reported the rate of MDR in a range of 41.0%–67.7% [ 9 , 20 , 28 , 52 , 60 ] while lower than some other findings [ 8 , 10 ]. In this study, the prevalence of MDR E. coli and K. pneumoniae was 59.3% and 48.8% respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike chromosomal mutation, acquisition of mcr is a matter of serious concern because of its potential transferability, as the gene is spread rapidly through the horizontal transfer at a higher rate than occurring through spontaneous mutation [ 18 ]. In addition, plasmids resistant to multiple classes of antibiotics can be transferred to other bacteria [ 19 , 20 ]. Elevated endemicity of mcr genes all over the world in a short span of time is attributable to their ability to proliferate at a higher pace [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 11.9% of the samples showed growth positivity. However, higher rates of growth positivity have been reported in similar studies in Nepal [20,21,22,23]. In this study, the highest number of growth was observed in the urine sample which was in agreement with that reported by GC et al [21] and Gurung et al [24].…”
Section: Discussionsupporting
confidence: 92%
“…K. pneumoniae was the dominant isolate, followed by E. coli and Acinetobacter spp. GC et al [21], Aryal et al [22], and Guragain et al [25] reported a 157 higher prevalence of E. coli followed by K. pneumoniae. Karn et al [20] reported a lower both sexes; however, culture positivity was higher for females than males in the urine sample, and 160 a higher prevalence of E. coli and K. pneumoniae was observed.…”
Section: Discussionmentioning
confidence: 99%
“…in our study. Binod et al [ 34 ], Aryal et al [ 35 ], and Guragain et al [ 39 ] reported a higher prevalence of E . coli followed by K .…”
Section: Discussionmentioning
confidence: 99%